Logodiversity and Translation - Aubert, Francis (Meta, 1996)
AbstractThe author defines logodiversity as an affinity between biodiversity and linguistic and cultural diversity. He looks at translation as both an instrument for the preservation of logo-diversity and as a contributing factor to the silencing of human polyphony.